Caspase-11 promotes high-fat diet-induced NAFLD by increasing glycolysis, OXPHOS, and pyroptosis in macrophages - Drummer, Charles; Saaoud, Fatma; Jhala, Nirag C.; Cueto, Ramon; Sun, Yu; Xu, Keman; Shao, Ying; Lu, Yifan; Shen, Huimin; Yang, Ling; Zhou, Yan; Yu, Jun; et al. (Frontiers in Immunology, 2023)
Non-alcoholic fatty liver disease (NAFLD) has a global prevalence of 25% and is a leading cause of cirrhosis and hepatocellular carcinoma. NAFLD encompasses a disease continuum from steatosis with or without mild inflammation (non-alcoholic fatty liver), to non-alcoholic steatohepatitis (NASH). Caspases are a family of cysteine proteases, most of which mediate regulated cell death (pyroptosis). Caspase-11 can cleave gasdermin D (GSDMD) to induce pyroptosis and specifically defends against bacterial pathogens that invade the cytosol. However, it’s still unknown whether high fat diet (HFD)-facilitated gut microbiota-generated cytoplasmic lipopolysaccharides (LPS) activate caspase-11 and promote NAFLD. Here, we show that HFD increases the expression of caspase-11, GSDMD, interleukin-1β, guanylate-binding proteins, and promotes NAFLD in WT mice. Caspase-11 deficiency decreases bone marrow monocyte-derived macrophage (MDM) pyroptosis (inflammatory cell death) and inflammatory monocyte (IM) surface GSDMD expression, re-programs liver transcriptomes, and reduces HFD-induced NAFLD. Caspase-11 deficiency decreased extracellular acidification rates (glycolysis) and oxidative phosphorylation (OXPHOS) in inflammatory fatty acid palmitic acid-stimulated macrophages, indicating that caspase-11 significantly contributes to maintain dual fuel bioenergetics- glycolysis and OXPHOS for promoting pyroptosis in macrophages. These results provide novel insights on the roles of the caspase-11-GSDMD pathway in promoting hepatic macrophage inflammation and pyroptosis, and novel targets for future therapeutic interventions involving the transition of NAFLD to NASH, hyperlipidemia, type-II diabetes, metabolic syndrome, metabolically healthy obesity, atherosclerotic cardiovascular diseases, autoimmune diseases, liver transplantation, and hepatic cancers.